Analyzing Watershed Carrying Capacity Based on Spatial Utilization and Built Environment Investment Performance in Tropical Watersheds - Muhsimin; Kahirun; Siwi, La Ode; Yunus, Lukman; La Ode Muhammad Erif (Universitas Jember, 2026)
The Wanggu Watershed (DAS), located in the center of Kendari City, tends to experience development pressure due to uncontrolled land use along with increasing urban needs and infrastructure. The research aims to analyze the carrying capacity of the Wanggu Watershed based on water infrastructure investment and spatial utilization. The research method used is based on the Ministry of Forestry Regulation No. P.61/Menhut-II/2014 Concerning Monitoring and Evaluation of Watershed Management. The analysis data used includes population, value of water building investment, area of vegetation cover, area of protected areas in the watershed, and land area with a slope of 0–250. The results show that building investment in the Wanggu Watershed is in a medium urban area (224,225 inhabitants), the value of water building investment has a very high class (Rp. 73,89 billion), and the classification of the carrying capacity value of watershed building investment shows a poor class (125). Land use in the protected area of the Wanggu Watershed has a poor class (27%) due to the low level of protection in conservation areas, while cultivation areas show a very good class (106%), and the classification of the carrying capacity value of watershed land use shows a good class (87.5). This indicates that the use of area functions is in accordance with its designation. Strengthening aspects of spatial planning policies and controlling the use of protected areas need to be improved to ensure sustainable and continuous management of the Wanggu Watershed.